Penyelenggaraan Administrasi Kepegawaian di Badan Kepegawaian Daerah (BKD) Kabupaten Kepulauan Sula - Liambana, Jumardin; Rompas, Welson; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT :This study aims to determine how the administration of the Organization in terms of personnel,especially in the district of Sulu Islands Regional Employment Board.This study used qualitative methods. The informants were 10 officers / employees at BKD are: headof the agency / secretary (1), the head of the field (3), and the head of the sub-areas (4), and the staff /implementers (2). Data collection techniques used were interviews. The data analysis was done by usingqualitative analysis interactive model of Miles and Hubermann.The results showed that: (1) The process of implementation of recruitment at BKD Sula Islandsbased on the determination of the formation of a minister according to regulations, and theimplementation process of recruitment of employees at BKD today already using the system CAT,although the implementation of recruitment/employess has been running well, but not maximized. (2) Theimplementation process of selection for placement of employees in structural positions is implemented inaccordance with the applicable legislation, but not maximum, because there are still weaknesses, and notall the structural officials meet in full all the main requirements for certain structural position as set outin PP.No .13 of 2002 on Hiring in structural positions.Based on the results of these studies conclude that: (1) the implementation process of recruitmentin BKD Sula Islands based regulations, but implementation of the recruitment system using CAT, so thatthe implementation of recruitment in Sula Islands is not maximized. (2) Selection process staffing in thestructural position in BKD Sula Islands in general are good, but not maximized because there are stillsome things that are required by the regulations have not been fully implemented.Based on the results of this study, it is necessary to put forward some suggestions: (1) To improvethe effectiveness of the implementation process of recruitment/civil servant in the Government of SulaIslands need to further expand facilities such as electronic instruments, WFI, and the room (a) needed forthe implementation of recruitment employee/civil servant using CAT systems (Computer Assisted Test)can run up. (2) It is expected that the selection process of the placement of employees in the structuralposition in lingungan Sula Islands Government should really sesui with the requirements stipulated inGovernment Regulation No. 13 of 2002 on Hiring in structural positions, and/selection process tominimize the placement of employees in structural positions in the Government of Sula Islands fore letconducted openly, namely through the auction system positions that have been implemented in someareas.Keywords: Recruitment, Placement Officer, structural positions.